"I have the right to feel safe": Evaluation of a school-based child sexual abuse prevention program in Ecuador. (May 2019) - Bustamante, Gabriela; Andrade, María Soledad; Mikesell, Caley; Cullen, Clara; Endara, Pablo; Burneo, Verónica; Yépez, Paola; Avila Saavedra, Soledad; Ponce, Paulina; Grunauer, Michelle
Abstract: Background: Child sexual abuse (CSA) is a complex public health problem that has lifelong implications for children's wellbeing. Interventions may provide children strategies to protect themselves against CSA, but few have been studied in Latin America. Objective: Evaluate the immediate and medium-term impact of a 10-week educational program on children's knowledge of CSA self-protection strategies in Ecuador. Participants and settings: Children aged 7–12 years from six public elementary schools in Ecuador were cluster-randomized to either receive the intervention between October and November 2016 (Group 1, k = 4) or between March and April 2017 (Group 2, k = 2). Methods: To assess CSA knowledge, a random sample of students completed a questionnaire at three time points: 1) initial: before any group received the intervention, 2) intermediate: immediately after Group 1 completed the program but before Group 2 started it, and 3) final: after Group 2 completed the program. We evaluated changes in scores using mixed linear regression models with school as a clustering variable and adjusted degrees of freedom (df = 4). Results: Pre-post effect estimates at program completion adjusted for age, sex and clustering by school were 6.5% (95% CI: 2.9, 10.0) and 6.8% (95% CI 3.0, 10.7) for Groups 1 and 2, respectively. Scores did not change among children who had not yet received the intervention at intermediate evaluation (0.94%, 95%CI: −6.0, 7.9). Children in Group 1 maintained the scores six months after the program ended. Conclusions: The self-protection program increased and maintained CSA knowledge six months after the intervention finished.